2012
DOI: 10.1007/s11999-012-2277-8
|View full text |Cite
|
Sign up to set email alerts
|

Are Shoulders with A Reverse Shoulder Prosthesis Strong Enough? A Pilot Study

Abstract: BackgroundIt has been suggested that limited active ROM of reverse shoulder prostheses relates to lack of strength. However, the postoperative strength has not been quantified.Questions/purposesWe therefore measured joint torques in patients with reverse shoulder prostheses and correlated torques with functional scores.MethodsWe recruited 33 patients (age, 72 ± 8 years) with a reverse prosthesis (37 shoulders, 21 primary and 16 revisions). We obtained Constant-Murley, DASH, and Simple Shoulder Test ([D]SST) sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…Because most functional activities are dynamic, evaluating isokinetic shoulder strength may be more appropriate when relating strength to functional performance and clinical outcome. In 2012, isokinetic strength measurements after RSA have been described (Alta et al, 2012), but similar data have not yet been reported for TSA patients.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Because most functional activities are dynamic, evaluating isokinetic shoulder strength may be more appropriate when relating strength to functional performance and clinical outcome. In 2012, isokinetic strength measurements after RSA have been described (Alta et al, 2012), but similar data have not yet been reported for TSA patients.…”
Section: Introductionmentioning
confidence: 84%
“…It is not completely clear if this difference is only caused by the type of prosthesis, or also by the (isokinetic) force generating capacity or a combination of both. Previous research (Bergmann et al, 2008) suggested that the limited glenohumeral motion of the RSA seems to be the result of a lack of joint torque generation, with moderate correlations between post-operative clinical outcome scores (Constant-Murley, DASH and SST) and the abduction and external rotation torques (Alta et al, 2012). Therefore, the evaluation of isokinetic shoulder strength after RSA in comparison to TSA patients may be of interest in modeling dynamic upper extremity function and may supply more specific information on the influence of the type of prosthesis on the force generating capacity, particularly where comparative data are only limited available (Puskas et al, 2013) for those two clinical scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations